Preparation method of lithium-rich manganese-based positive electrode material

By modifying the lithium-rich manganese-based positive electrode material, the surface structure of spinel phase and oxygen vacancy is formed, which solves the problems of low efficiency, poor rate performance, poor cycle stability and voltage attenuation of the material in the first circle, and achieves the dual improvement of the specific capacity and cycle performance of the material.

CN119725470APending Publication Date: 2025-03-28CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411930520.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In actual use, lithium-rich manganese-based positive electrode materials have problems such as low efficiency, poor rate performance, poor cycle stability and serious voltage attenuation, which limits their application.

Method used

By modifying the lithium-rich manganese-based positive electrode material by ozone, a surface structure composed of spinel phase and oxygen vacancy is formed, defects are introduced in the main structure, local orderly structure is regulated, and the structural stability of the material is improved.

Benefits of technology

Effectively inhibit irreversible oxygen release, stabilize the surface structure, and improve the specific capacity and circulation performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725470A_ABST
    Figure CN119725470A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material is one or more of a Co-free lithium-rich manganese-based positive electrode, a Ni-free lithium-rich manganese-based positive electrode or a Ni / Co-free lithium-rich manganese-based positive electrode; the lithium-rich manganese-based positive electrode material is placed in 5-20 wt% of ozone, the reaction temperature is 80-105 DEG C, and the ozone modified lithium-rich manganese-based positive electrode material is obtained. According to the lithium-rich manganese-based positive electrode material modified by ozone, a specific structure integrating a spinel phase and oxygen and air is formed on the surface of the material, defects of a main structure are enriched, and the disorder degree of cations is increased. The surface composed of the surface spinel phase and the oxygen vacancies can effectively inhibit irreversible oxygen release and stabilize the surface structure. Defects are introduced into the main body structure, and the regulated and controlled local ordered structure has the characteristic of high structural stability. The surface / main body structure with multifunctional components finally realizes double improvement of the specific capacity and circulation of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a method for preparing a lithium-rich manganese-based positive electrode material. Background Art

[0002] With the rapid development of new energy vehicles and energy storage systems, layered oxide cathode materials (such as lithium cobalt oxide, ternary cathode, etc.) with relatively high platform voltage and specific capacity have been widely used in the field of commercial lithium-ion batteries. However, the low specific capacity of traditional cathode materials can no longer meet the growing range requirements of electric vehicles. Therefore, the development of a new generation of high energy density cathode materials is an important issue that the current new energy field needs to face.

[0003] Lithium-rich manganese-based cathode materials have ultra-high specific capacity (>250mAh / g) and high operating voltage of 4.8V, and are considered to be strong candidates for high specific energy cathode materials. It is worth noting that the high capacity of lithium-rich manganese-based cathode materials comes from the activation of Li2MnO3 at high voltage >4.5V, which makes the transition metal (TM 2+ / 3+ / 4+ ) and lattice oxygen (O 2- ) participate in charge compensation together. However, due to the poor reversibility and stability of anion redox reactions and low electrochemical reaction kinetics, lithium-rich manganese-based cathode materials still have the following key problems in actual use: 1) low first-cycle coulomb efficiency due to oxygen release and irreversible movement of Li2O in the lattice; 2) poor rate performance due to low electron and lithium ion conductivity; 3) poor cycle stability; 4) severe voltage decay during the cycle. These problems have seriously restricted the further application of lithium-rich manganese-based cathode materials.

[0004] In response to the above problems, surface modification has attracted the attention of many researchers due to its advantages such as low cost and high controllability, and is regarded as an effective strategy to improve the electrochemical performance of lithium-rich manganese-based cathode materials. Currently, many modification methods (material structure design, element doping and surface coating) have been developed, but it is worth noting that these modification methods are often complex in process, high in cost, and have high bottlenecks in achieving large-scale application. At the same time, these modification methods are difficult to directly solve the problems of high first irreversible capacity, poor cycle performance, poor rate performance, severe voltage decay and voltage hysteresis of lithium-rich manganese-based cathode materials. Therefore, it is crucial to develop a modification technology that is simple in process and can directly and effectively achieve overall regulation of the surface and bulk structure properties of the material, and then develop high-capacity, long-cycle, commercially available lithium-rich manganese-based cathode materials. Summary of the invention

[0005] In order to solve the above problems, the present invention aims to provide a method for preparing a lithium-rich manganese-based positive electrode material. The preparation method modifies the lithium-rich manganese-based positive electrode material with ozone, and the surface of the obtained material forms a specific structure in which a spinel phase and oxygen vacancies are integrated. The main structure is defect-enriched, and the degree of cation disorder is increased. The surface composed of the surface spinel phase and oxygen vacancies can effectively inhibit irreversible oxygen release and stabilize the surface structure, so that the material specific capacity and cycle are double improved. Compared with traditional lithium-containing positive electrode materials, ozone at an appropriate concentration does not have a significant oxidizing effect on traditional lithium-containing positive electrode materials.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material is one or more of a Co-free lithium-rich manganese-based positive electrode, a Ni-free lithium-rich manganese-based positive electrode, or a Ni / Co-free lithium-rich manganese-based positive electrode; the lithium-rich manganese-based positive electrode material is placed in 5-20wt% ozone at a reaction temperature of 80-105°C to obtain an ozone-modified lithium-rich manganese-based positive electrode material.

[0008] The molar ratio of lithium-rich manganese-based cathode material to ozone is 1:5 to 5:1. The molecular formula of lithium-rich manganese-based cathode material is xLi2MnO3·(1-x)LiMO2, where M is one or more of transition metals Ni, Co and Mn, and 0<x<1.

[0009] The lithium-rich manganese-based positive electrode material is placed in 5-20wt% ozone for 600-900 minutes.

[0010] 5-20 wt% of ozone is introduced by ozone-loaded gas, and the ozone-loaded gas is one of nitrogen atmosphere, argon atmosphere, oxygen atmosphere, hydrogen-argon mixed atmosphere, hydrogen-nitrogen mixed atmosphere or nitrogen-argon mixed atmosphere.

[0011] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0012] The ozone-modified lithium-rich manganese-based positive electrode material of the present invention has a specific structure of spinel phase and oxygen vacancies on the material surface, the main structure is defect-enriched, and the degree of cation disorder is increased. The surface composed of the surface spinel phase and oxygen vacancies can effectively inhibit irreversible oxygen release and stabilize the surface structure. The main structure introduces defects, and the regulated local ordered structure has the characteristics of high structural stability. The surface / main structure with multifunctional components ultimately achieves a dual improvement in material specific capacity and cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0014] Figure 1 The first discharge curves of Examples 1, 2, 3 of the present invention and the comparative sample at an operating voltage of 2.5-4.8V are shown.

[0015] Figure 2 It is a typical first cycle charge and discharge curve diagram corresponding to Example 4 of the present invention and its comparative sample at an operating voltage of 2.5-4.8V. DETAILED DESCRIPTION

[0016] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0017] Example 1 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn 0.57 O2 ozone treatment

[0018] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 100°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 10wt% ozone into the reaction chamber. After reacting for 600s, pass nitrogen to purge for 90s to take the residual ozone out of the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0019] The above materials were mixed and ground with conductive carbon black and halide solid electrolyte to obtain a positive electrode for solid-state batteries. The above positive electrode was assembled into an all-solid-state battery in a glove box filled with argon, in which a metal lithium-indium alloy was used as the negative electrode, and a halide solid electrolyte and a sulfide solid electrolyte double layer were used as the electrolyte. The assembled all-solid-state battery was taken out of the glove box for subsequent electrochemical performance testing. The charge and discharge curves at a current density of 200mAh / g are shown in Figure 2. Figure 1 shown.

[0020] Example 2 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn 0.57 O2 ozone treatment

[0021] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 100°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 10wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to remove the residual ozone from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0022] The above materials were mixed and ground with conductive carbon black and halide solid electrolyte to obtain a positive electrode for solid-state batteries. The above positive electrode was assembled into an all-solid-state battery in a glove box filled with argon, in which a metal lithium-indium alloy was used as the negative electrode, and a halide solid electrolyte and a sulfide solid electrolyte double layer were used as the electrolyte. The assembled all-solid-state battery was taken out of the glove box for subsequent electrochemical performance testing. The charge and discharge curves at a current density of 200mAh / g are shown in Figure 2. Figure 1 shown.

[0023] Example 3 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn 0.57 O2 ozone treatment

[0024] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 105°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 15wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to remove the residual ozone from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0025] The above materials were mixed and ground with conductive carbon black and halide solid electrolyte to obtain a positive electrode for solid-state batteries. The above positive electrode was assembled into an all-solid-state battery in a glove box filled with argon, in which a metal lithium-indium alloy was used as the negative electrode, and a halide solid electrolyte and a sulfide solid electrolyte double layer were used as the electrolyte. The assembled all-solid-state battery was taken out of the glove box for subsequent electrochemical performance testing. The charge and discharge curves at a current density of 200mAh / g are shown in Figure 2. Figure 1 shown.

[0026] Example 4 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn 0.57 O2 ozone treatment

[0027] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 105°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 5wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to remove the residual ozone from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0028] Example 5 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn 0.57 O2 ozone treatment

[0029] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 105°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 20wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to remove the residual ozone from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0030] Example 6 Lithium-rich manganese-based positive electrode Li 1.14 Ni 0.29 Mn0.57 O2 ozone treatment

[0031] The lithium-rich positive electrode material is treated with ozone. (1) Weigh 15g of lithium-rich positive electrode material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove water adsorbed on the surface. (2) Place the dried lithium-rich positive electrode material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 80°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 15wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to take the residual ozone out of the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium-rich material.

[0032] Comparative Example 1

[0033] Similar to Example 3, except that no ozone treatment was performed

[0034] Comparative Example 2 Ozone treatment of lithium cobalt oxide LiCoO2 material

[0035] The lithium cobalt oxide material is treated with ozone. (1) Weigh 15g of lithium cobalt oxide material, place it in a vacuum oven, and vacuum dry it at 80°C for 6h to remove the water adsorbed on the surface. (2) Place the dried lithium cobalt oxide material into an atomic layer deposition reaction bottle, place the reaction bottle into the reaction chamber, and evacuate it to below 0.1mPa. (3) Raise the temperature to 105°C in the reaction chamber, 85°C in the pipeline, and keep the precursor ozone at room temperature. (4) Turn on the rotary switch to heat the reaction bottle evenly. After the temperature reaches the set value, use nitrogen as the carrier gas, open the ozone valve for 1s, and pass 15wt% ozone into the reaction chamber. After reacting for 900s, pass nitrogen to purge for 90s to remove the residual ozone from the reaction chamber. (2)-(4) is a complete cycle. Repeat the above steps 60 times to obtain the modified lithium cobalt oxide material.

[0036] The above materials were mixed and ground with conductive carbon black and halide solid electrolyte to obtain a positive electrode for solid-state batteries. The above positive electrode was assembled into an all-solid-state battery in a glove box filled with argon, in which a metal lithium-indium alloy was used as the negative electrode, and a halide solid electrolyte and a sulfide solid electrolyte double layer were used as the electrolyte. The assembled all-solid-state battery was taken out of the glove box for subsequent electrochemical performance testing. The charge and discharge curves at a current density of 200mAh / g are shown in Figure 2. Figure 2 shown.

[0037] Comparative Example 3

[0038] Similar to Comparative Example 2, except that no ozone treatment was performed.

[0039] It can be seen from Comparative Example 1 and Examples 1, 2, and 3 that the specific capacity release of Comparative Example 1 is 242 mAh / g, and the specific capacity of Example 3 reaches 345 mAh / g. Ozone treatment has a very obvious benefit on the capacity release and the first coulombic efficiency improvement of the lithium-rich manganese-based positive electrode material, especially on the redox performance of oxygen in the lithium-rich manganese-based positive electrode, which is significantly different from other prior arts for conventional layered positive electrode materials such as lithium cobalt oxide and ternary positive electrodes. Based on this, we also performed ozone treatment on the conventional layered positive electrode material lithium cobalt oxide. It can be seen from Comparative Examples 2 and 3 that even after ozone treatment, the effect is not obvious. This shows the innovation and foresight of the present invention.

[0040] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is one or more of a Co-free lithium-rich manganese-based positive electrode, a Ni-free lithium-rich manganese-based positive electrode or a Ni / Co-free lithium-rich manganese-based positive electrode; the lithium-rich manganese-based positive electrode material is placed in 5-20wt% ozone at a reaction temperature of 80-105°C to obtain an ozone-modified lithium-rich manganese-based positive electrode material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of lithium-rich manganese-based positive electrode material to ozone is 1:5 to 5:

1.

3. The preparation method according to claim 1, characterized in that: The molecular formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiMO2, where M is one or more of the transition metals Ni, Co and Mn, and 0<x<1.

4. The preparation method according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material is placed in 5-20wt% ozone for 600-900 minutes.

5. The preparation method according to claim 1, characterized in that: 5-20 wt% of ozone is introduced by ozone-loaded gas, and the ozone-loaded gas is one of nitrogen atmosphere, argon atmosphere, oxygen atmosphere, hydrogen-argon mixed atmosphere, hydrogen-nitrogen mixed atmosphere or nitrogen-argon mixed atmosphere.